Addressing the mental health concerns of migrant workers during the COVID-19 pandemic: An experiential account. (November 2021) - Chander, Rakesh; Murugesan, Manisha; Ritish, Daniel; Damodharan, Dinakaran; Arunachalam, Vikram; Parthasarathy, Rajani; Raj, Aravind; Sharma, Manoj Kumar; Manjunatha, Narayana; Bada Math, Suresh; Kumar, Channaveerachari Naveen
The COVID pandemic has affected the world in a drastic manner taking a toll of not only human lives but also the economy and lifestyle. Of all the population suffering, the underprivileged and vulnerable groups have faced the maximum economic burden. Within India, an ample quota of people migrates annually for elementary occupations in service, sales, building and domestic industries. Generally, they are exposed to discrimination, work-rights exploitation and job insecurity. The onset of COVID 19 has accentuated these issues in unprecedented ways. The Apex Court of the country took note of this plight and gave directions to the governments to take care of the immediate needs of the migrant workers. This article attempts to reflect the mental health concerns of the migrant workers who were temporarily sheltered at relief camps across Bengaluru city in the state of Karnataka, during the ongoing COVID pandemic. The article ends with giving recommendations